2017
DOI: 10.4103/2249-4863.222009
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of hepatitis B among healthy population: A community-based survey from two districts of Gujarat, India

Abstract: Background:Hepatitis B is the world's most common blood-borne viral infection, accounting for 2 billion infections, 350 million carriers, and 6 lakh deaths annually. Country like India still harbors approximately 30–60 million hepatitis B virus (HBV) carriers. A modest estimate would put the number of deaths occurring due to HBV infection per year in India to around 100,000. To prevent transmission and progression of the disease, proper community awareness including prevention is necessary. Therefore, this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
3
9
0
Order By: Relevance
“…In this study, 23.1% reported history of blood transfusion out of which 17.9% had transfusion after screening. This study demonstrates that only 10.3% were vaccinated for Hepatitis B while 89.7% were not vaccinated which is somewhat similar to a study conducted in India in 2017 where only 20% were vaccinated (16). This study revealed that only 5.9% participants were taking treatment for Hepatitis B of which 3.4% took treatment from doctors, 1.7% from hakeem and 0.9% preferred homeopathic treatment.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, 23.1% reported history of blood transfusion out of which 17.9% had transfusion after screening. This study demonstrates that only 10.3% were vaccinated for Hepatitis B while 89.7% were not vaccinated which is somewhat similar to a study conducted in India in 2017 where only 20% were vaccinated (16). This study revealed that only 5.9% participants were taking treatment for Hepatitis B of which 3.4% took treatment from doctors, 1.7% from hakeem and 0.9% preferred homeopathic treatment.…”
Section: Discussionsupporting
confidence: 84%
“…The majority (89.3%) of the participants were aware that HBV vaccine provides protection against HBV infection, however awareness may not reflect knowledge since only 20.2% replied that the vaccine provides (after administration of the three doses) > 90% protection to infants, children, and adults immunized before being exposed to the virus. This contradicts the results in the research of Yasobant et al (27) which two thirds of the population in Gujarat was found to be unaware about Hepatitis B and its vaccine, as well as, the results of a research done in Mumbai that showed that only less than 5% of the participants stated that they were aware of the disease (28). In addition, only 43.5% replied that vaccine is safe and does not cause any side effects and that the HB vaccine is not only one of the most effective but also one of the safest vaccine ever developed while side-effected have rarely been reported (Saridi et al, 2011).…”
Section: Discussionmentioning
confidence: 60%
“…Few studies reported similar findings with regards to the knowledge of routes of transmission via blood, infected needles and sexual transmission. 12,16 Other studies have reported that higher proportion of their populations knew about the routes of transmission of HBV. [17][18][19] About 8.7% of our respondents were aware that transmission of HBV can take place from mother to child during pregnancy.…”
Section: Resultsmentioning
confidence: 99%